Four-dimensional isotopic approach to identify perchlorate sources in groundwater: Application to the Rialto-Colton and Chino subbasins, southern California (USA). (October 2018) - Hatzinger, Paul B.; Böhlke, J.K.; Sturchio, Neil C.; Izbicki, John; Teague, Nicholas
Abstract: Perchlorate (ClO4 − ) in groundwater can be from synthetic or natural sources. Natural sources include ClO4 − associated with historical application of imported natural nitrate fertilizer from the Atacama Desert of Chile, and indigenous ClO4 − that accumulates locally in arid regions from atmospheric deposition. The Rialto-Colton groundwater subbasin, 80 km east of Los Angeles, California, includes two mapped ClO4 − plumes from known military/industrial sources. Larger areas downgradient from those plumes, and in the Chino subbasin to the southwest, also contain ClO4 − . Perchlorate from wells was analyzed for chlorine and oxygen stable isotope ratios (δ 37 Cl, δ 18 O, Δ 17 O) and radioactive chlorine-36 ( 36 Cl) isotopic abundance, along with other geochemical, isotopic, and hydrogeologic data. Isotopic data show that synthetic ClO4 − was the dominant source within the mapped plumes. Downgradient from the mapped plumes, and in the Chino subbasin, the dominant source of ClO4 − was related to past agricultural use of Chilean (Atacama) nitrate fertilizer. The 36 Cl and δ 18 O data indicate that wells having predominantly synthetic or Atacama ClO4 − also contained small fractions of indigenous ClO4 − . Little or no differences were observed in isotopic composition or ClO4 − source with depth in depth-dependent data from selected wells. Indigenous ClO4 − was most evident in upgradient wells having ClO4 − concentrations <1 μg/L, consistent with its occurrence as a background constituent throughout the region. Stable isotope ratios of chlorine and oxygen and 36 Cl isotopic abundance data provided relatively unambiguous discrimination of synthetic and Atacama sources in most wells having ClO4 − concentrations greater than 1 μg/L. Highlights: Four different isotopic methods were applied for forensic perchlorate analysis. Perchlorate from three different sources was documented in the study area. 36 Cl/Cl proved valuable as a measure of natural indigenous perchlorate.